SISTEM PENDUKUNG KEPUTUSAN PENERIMA BEASISWA MENGGUNAKAN METODE ANALYTHICAL HIERARCHY PROCESS PADA STT MUSI - Wijaya, Andri; Wulan P, Maria (Proceedings of KNASTIK, 2012)
In determining the scholarship recipients at the Sekolah Tinggi Teknik Musi there areseveral criteria used to conduct the assessment. Criteria - such criteria as grade pointaverage (GPA), parental income, elderly dependents, semester, TOEFL, and religion.For efficiency and effectiveness of work then the right decision making is needed.Thisfinal report aims to create a decision support system using the method of AnalyticHierarchy Process to assist decision makers in determining who will receivescholarships based on established criteria. Decision support system scholarshiprecipient has the ability to analyze the scholarship recipients by using AHP method,which will be comparisons between the criteria with other criteria and alternatives inthis case the student compared to each other to obtain comparison graphs.The methodused in the writing of this report is a waterfall method by conducting interviews andreferences to obtain data. Making this system starts from the analysis of systems usingmodeling in the form, Context Diagram, DFD, process specifications, data dictionaryand ERD, design, implementation, and testing the system. All the stages passedthrough, except for installation and maintenance phases. The implementation usingprogramming language Visual Basic 6.0 and SQL Server 2000 database. Testsconducted only limited to the functional system of just using black-box testing. It isexpected that awardees decision support system can be implemented at Sekolah TinggiTeknik Musi.